POLA PENYEBARAN MINYAK DI PERAIRAN SELAT RUPAT DUMAI, RIAU. - Thamrin Thamrin; Khairil Anwar; Mubarak Mubarak (Jurnal Ilmu Lingkungan, 2007)
Observation of oil concentration was conducted to know pattern of oil distribution in Rupat Strait in front of Dumai City, Riau. Samples were collected on 19 sampling side on Rupat Strait in June 2007, and the samples transported to Chemistry Laboratoty, FMJPA, Riau University before data were analyzed by using software surfer. Highest concent ration of oil was detected around harbor of Duinai City and distribu ted to both northern and southern from around the Harbor. Concentration pattern of oil distribution decreased toward all directions from a round harbor, and may be controlled by tidal current which cause oil distribution occurred horizontally with the coast of Dumai City side was longer thami vertical distribution from Dumai side to Rupat Island.